Investigation of Effect of Phenol on Antioxidant Parameters in Scaly Carp (Cyprinus Carpio) - Yonar, Serpil Mişe; Yonar, M. Enis (Durmuş Ali ARSLAN, 2024)
Phenol, an aromatic chemical commonly found in domestic and industrial waste, adversely affects invertebrates and vertebrates when it enters aquatic ecosystems. With the increasing demand for agricultural chemicals, large amounts of phenol are released directly into the environment as a by-product. Phenol and its derivatives tend to persist in the environment for longer periods of time, posing a threat to both humans and the aquatic ecosystems. The aim of this study was to investigate the effects of different concentrations of phenol on oxidative stress and some antioxidant parameters in scaly carp (Cyprinus carpio). Three different concentrations of phenol (0.10, 0.25 and 0.50 ppm) were applied to the fish for 48 hours. At the end of the experiment, malondialdehyde levels as an indicator of oxidative stress and antioxidant parameters (catalase, glutathione peroxidase and glutathione-S-transferase activities and reduced glutathione levels) were analyzed in spleen samples taken from fish. It was found that tissue malondialdehyde levels of the phenol-administered groups were statistically increased compared to the control group (p < 0.05). While tissue catalase and glutathione peroxidase activities and reduced glutathione levels were found to be significantly decreased in the phenol-treated groups compared with the control group, tissue glutathione-S-transferase activities were found to be statistically significantly increased (p < 0.05).

Evsel ve endüstriyel atıklarda yaygın olarak bulunan aromatik bir kimyasal olan fenol, su ekosistemlerine girdiğinde omurgasız ve omurgalıları olumsuz etkilemektedir. Tarımsal kimyasallara olan talebin artmasıyla birlikte, büyük miktarda fenol doğrudan bir yan ürün olarak çevreye salınmaktadır. Fenol ve türevleri çevrede daha uzun süre kalma eğilimindedir ve bu da hem insanlar hem de su ekosistemi için bir tehdit oluşturmaktadır. Bu çalışmada farklı konsantrasyonlardaki fenolün pullu sazanda (Cyprinus carpio) oksidatif stres ve bazı antioksidan parametreler üzerine etkisini araştırmak amaçlandı. Üç farklı konsantrasyonda fenol (0,10, 0,25 ve 0,50 ppm) 48 saat süreyle balıklara uygulandı. Deneme sonunda balıklardan alınan dalak örneklerinde oksidatif stresin bir göstergesi olarak malondialdehit düzeyleri ile antioksidan parametreler (katalaz, glutatyon peroksidaz, glutatyon-S-transferaz aktiviteleri ve redükte glutatyon düzeyi) analiz edildi. Fenol verilen grupların doku malondialdehit düzeylerinin kontrol grubuna göre istatistiksel olarak yükseldiği belirlendi (p < 0,05). Fenol uygulanan gruplarda doku katalaz ve glutatyon peroksidaz aktiviteleri ve redükte glutatyon düzeylerinin kontrol grubuna göre anlamlı olarak azaldığı tespit edilirken, doku glutatyon-S-transferaz aktivitelerinin istatistiksel olarak önemli düzeyde arttığı belirlendi (p < 0,05).
Antioksidan Parametrelere Fenolün Etkisinin Pullu Sazan (Cyprinus carpio)’ da Araştırılması
Keywords: Aquaculture and Fisheries (Other); Sucul Kültür ve Balıkçılık (Diğer)